Exploring User Experiences of Chat GPT and Google Gemini AI : A SUS and EUCS Approach - Fausta Rizky Abriansah; Nanda Dwi Kurniawan; Praditya Rendi Ferdian; Daffa Nurin Nabil Ma'arif; Azmi Maulana Firdaus; Pratama Angga (Journal of Information Technology, Computer Engineering and Artificial Intelligence (ITCEA), 2024)
This study evaluates user experience and satisfaction of two AI platforms, Chat GPT and Google Gemini, using the System Usability Scale (SUS) and End-User Computing Satisfaction (EUCS) approaches. The study involved 78 respondents from diverse backgrounds who provided evaluations based on five main dimensions of usability (Learnability, Efficiency, Memorability, Error, Pleasantness) and five dimensions of user satisfaction (Content, Accuracy, Format, Ease of Use, Timeliness). The results show that both platforms achieved a "Satisfied" category with an average usability and satisfaction score above 3.75. The lowest scores were recorded in Error and Timeliness variables, while Learnability and Format showed the highest scores. This study also revealed a significant positive correlation between usability and user satisfaction, providing recommendations for improvements in Error and Timeliness areas. These findings offer valuable insights for developing more user-friendly and responsive AI platforms in the future.